2013
DOI: 10.7554/elife.01228
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic translocation of the retinoblastoma protein disrupts sarcomeric organization

Abstract: Skeletal muscle degeneration is a complication arising from a variety of chronic diseases including advanced cancer. Pro-inflammatory cytokine TNF-α plays a pivotal role in mediating cancer-related skeletal muscle degeneration. Here, we show a novel function for retinoblastoma protein (Rb), where Rb causes sarcomeric disorganization. In human skeletal muscle myotubes (HSMMs), up-regulation of cyclin-dependent kinase 4 (CDK4) and concomitant phosphorylation of Rb was induced by TNF-α treatment, resulting in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 45 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…Importantly, inhibition of autophagy rescues this phenotype even in the absence of pRB function (51). Intriguingly, Araki et al have recently demonstrated that loss of nuclear localization by pRB interferes with sarcomere structure in skeletal muscle, leading to a nonapoptotic cell death (52). This may offer a nontranscriptional explanation of our phenotype, as loss of E2F binding likely reduces pRB anchorage in the nucleus.…”
Section: Discussionmentioning
confidence: 79%
“…Importantly, inhibition of autophagy rescues this phenotype even in the absence of pRB function (51). Intriguingly, Araki et al have recently demonstrated that loss of nuclear localization by pRB interferes with sarcomere structure in skeletal muscle, leading to a nonapoptotic cell death (52). This may offer a nontranscriptional explanation of our phenotype, as loss of E2F binding likely reduces pRB anchorage in the nucleus.…”
Section: Discussionmentioning
confidence: 79%
“…Thus, the physiological function of Rb consists of two independent circuits (Figure S6D): hypo-phosphorylated Rb mainly binds and suppresses E2F1 to arrest cell cycle at G1 phase, while the hyper-phosphorylated species of Rb become loosely interacted with chromatin and partly translocates into the cytoplasm to bind and inhibit mTORC2 towards activating the Akt oncogenic signaling pathways. However, as Rb can impact mitochondrial biogenesis and function in cytoplasm (Araki et al, 2013; Attardi and Sage, 2013; Hilgendorf et al, 2013; Nicolay et al, 2015), future study is warranted to explore whether hyper-phosphorylated Rb also can indirectly affect mTORC2 through regulating mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the canonical function of Rb in regulating cell cycle progression in the nucleus, recent studies have also started to reveal a possible physiological role of Rb in the cytoplasm, such as regulating mitochondrial functions and disrupting sarcomeric organization (Araki et al, 2013; Hilgendorf et al, 2013; Nicolay et al, 2015). In support of these findings, the hyper-phosphorylated form of Rb has been observed in the cytoplasm of human cancers (Jiao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We reported recently that Rb causes disruption of the sarcomeric structure of skeletal muscle myotubes via its interaction with the formin protein mDia1 [113], an effector of RhoA [114]. This pathway is stimulated by the inflammatory cytokine TNF α .…”
Section: Rb Regulates Cell Adhesion Molecules and Downstream Pathwaysmentioning
confidence: 99%
“…Cytoplasmic Rb might contribute to cancer progression by promoting muscle atrophy. Indeed, cytoplasmic Rb was detected in atrophied tibialis anterior muscles, but not the normal muscles, of cancer patients [113]. …”
Section: Rb Regulates Cell Adhesion Molecules and Downstream Pathwaysmentioning
confidence: 99%